PENGETAHUAN, SIKAP, DAN PERSEPSI IBU HAMIL KEKURANGAN ENERGI KRONIS (KEK) MENGENAI MAKANAN TAMBAHAN (MT) - Ni Kadek Ayu Sriandewi; Kadek Tresna Adhi (ARCHIVE OF COMMUNITY HEALTH, 2023)
ABSTRACT Chronic Energy Deficiency is a condition in which the mother experiences a chronic lack of energy intake, causing health problems for the mother. Efforts made by the government in overcoming this problem through the provision of additional food. The purpose of the study was to determine the knowledge and perception of nutrition, as well as attitudes regarding additional food in pregnant women with chronic energy deficiency. This research is a quantitative descriptive study using a cross-sectional method. The research sample is pregnant women with chronic energy deficiency in Badung Regency. Research variables include age, education, working status, parity, family income, knowledge, attitudes, and perceptions. Data collection techniques using a questionnaire via google form and filling directly. The research analysis used univariate analysis. The result of this research is that the average sample is 26 years old and has a high school education (63.06%). Most (98.20%) of low parity and the majority of pregnant women with chronic energy deficiency do not work (64.86%). Family income (50.45%) is in the high category. Overall (99.10%) pregnant women with chronic energy deficiency have good knowledge about nutrition and (56.76%) have a good attitude regarding supplementary foods, and (54.95%) have positive perceptions about nutrition. Based on the results of the study, the puskesmas maximized the dissemination of information about pregnant women with chronic lack of energy and the benefits of consuming additional food through classes for pregnant women. In addition, further researchers can add variables such as taboo foods and beliefs that may be related to the consumption of supplementary foods in pregnant women with chronic energy deficiency. Keywords: knowledge, attitude, perception, pregnant women, chronic energy deficiency, supplementary food ABSTRAK Kurang Energi Kronis (KEK) merupakan keadaan ibu mengalami kekurangan asupan energi yang berlangsung menahun sehingga menimbulkan gangguan kesehatan pada ibu. Upaya yang dilakukan pemerintah dalam penanggulangan masalah tersebut melalui pemberian makanan tambahan. Tujuan penelitian untuk mengetahui pengetahuan dan persepsi gizi, serta sikap mengenai MT pada ibu hamil KEK. Penelitian ini merupakan penelitian deskriptif kuantitatif menggunakan metode cross-sectional. Sampel penelitian yaitu ibu hamil KEK di Kabupaten Badung. Variabel penelitian meliputi umur, pendidikan, status bekerja, paritas, pendapatan keluarga, pengetahuan, sikap, dan persepsi. Teknik pengumpulan data menggunakan kuesioner melalu google form dan pengisian secara langsung. Analisis penelitian menggunakan analisis univariat. Hasil penelitian yaitu rata-rata sampel berusia 26 tahun dan berpendidikan SMA (63,06%). Sebagian besar (98,20%) paritas rendah dan mayoritas ibu hamil KEK tidak bekerja (64.86%). Pendapatan keluarga (50,45%) termasuk katagori tinggi. Keseluruhan (99,10%) ibu hamil KEK memiliki pengetahuan baik mengenai gizi dan (56,76%) memiliki sikap yang baik terkait MT, serta (54,95%) memiliki persepsi positif mengenai gizi. Berdasarkan hasil penelitian yaitu puskesmas memaksimalkan penyebaran informasi mengenai ibu hamil KEK dan manfaat konsumsi MT melalui kelas ibu hamil. Selain itu, peneliti selanjutnya dapat menambahkan variable seperti makanan tabu dan keyakinan yang mungkin berhubungan dengan konsumsi MT pada ibu hamil KEK. Kata kunci: pengetahuan, sikap, persepsi, ibu hamil, KEK, MT